PyLAP/PHaRLAP HF Ray Tracing and SAMI3: Integration and Refactoring - Devin Diehl; Rachel Boedicker; Joseph Huba; Nathaniel A. Frissell (HamSCI Workshop 2024, 2024)
PyLAP is a high frequency (HF) ray tracing toolkit that is used to model radio wave propagation through the ionosphere. Currently PyLAP uses the empirical International Reference Ionosphere (IRI) model. In an effort to use PyLAP to observe more discrete structures in ionosphere that are otherwise unobservable with IRI, PyLAP is being Integrated with the Physics-based SAMI3 Model of the ionosphere. Along with this there will be an effort to refactor some of the current PyLAP codebase so that it is more readable and usable for anyone using the current system including both professional and citizen scientists.

Modeling the Ionosphere with SAMI3 (Invited Tutorial) - Joseph Huba (HamSCI Workshop 2023, 2023)
SAMI3 (Sami3 is Also a Model of the Ionosphere) is a global, comprehensive model of the ionosphere/plasmasphere system. It is based on the SAMI2 model developed at the Naval Research Laboratory (Huba et al., 2000). SAMI3 models the plasma and chemical evolution of seven ion species (H, He, N, O, N, NO and O). The ion temperature equation is solved for three ion species (H, He and O) as well as the electron temperature equation. Ion inertia is included in the ion momentum equation for motion along the geomagnetic field. The neutral composition and temperature can be specified by empirical models (e.g, NRLMSISE00, HWM14) or by first-principle atmosphere models (e.g., TIEGCM, WACCM-X, HIAMCM). SAMI3 uses a nonorthogonal, nonuniform, fixed grid. The grid is designed to optimize the numerical mesh so that the spatial resolution decreases with increasing altitude. SAMI3 can use an untilted or tilted dipole model of earth’s magnetic field, or an IGRF field model based on the Richmond apex model. A general overview of ionospheric physics and the SAMI3 model will be presented, as well as several applications of the code.